Peningkatan komitmen afektif berbasis Islamic work ethics, spiritual leadership dan perceived organizational support terhadap organizational citizenship behavior - Lutfi Nurcholis; Ibnu Khajar; Santi Retno Ayu Palupi (Jurnal Riset Ekonomi dan Bisnis, 2022)
Penelitian ini bertujuan untuk menganalisis secara empiris pengaruh Islamic Work Ethics, Spiritual Leadership dan Perceived Organizational Support terhadap Organizational Citizenship Behavior dengan Komitmen Afektif sebagai variabel intervening pada pegawai di Pengadilan Tinggi Jawa Tengah. Populasi yang digunakan adalah pegawai Pengadilan Tinggi Jawa Tengah dengan jumlah sampel sebesar 98 responden. Alat analisisnya adalah Partial Least Square. Urgensi penelitian ini adalah adanya perubahan dalam restrukturisasi organisasi yaitu pemisahan struktur kesekretariatan dan kepaniteraan pengadilan yang berdampak pada disharmonis hubungan Ketua dan Sekretaris, yang mempengaruhi rendahnya perilaku pegawai untuk mau bekerja secara ekstra role dalam menjalankan tugasnya, seperti saling bantu membantu dan bekerja sama dengan sesama pegawai. Kebaruan dalam penelitian ini adalah penambahan variabel komitmen afektif sebagai variabel mediasi dalam hubungan antara Islamic Work Ethics, Spiritual Leadership dan Perceived Organizational Support dengan Organizational Citizenship Behavior. Hasil pengujian menunjukkan bahwa Islamic Work Ethics, Spiritual Leadership dan Perceived Organizational Support berpengaruh positif signifikan terhadap Komitmen Afektif. Islamic Work Ethics, Spiritual Leadership, Perceived Organizational Support dan Komitmen Afektif berpengaruh positif signifikan terhadap Organizational Citizenship Behavior. Komitmen Afektif mampu menjadi variabel intervening antara Islamic Work Ethics terhadap Organizational Citizenship Behavior. Komitmen Afektif mampu menjadi variabel intervening antara Spiritual Leadership terhadap Organizational Citizenship Behavior. Komitmen Afektif mampu menjadi variabel intervening antara Perceived Organizational Support terhadap Organizational Citizenship Behavior.This study aims to examine and analyze empirically the influence of Islamic Work Ethics, Spiritual Leadership and Perceived Organizational Support on Organizational Citizenship Behavior with Affective Commitment as an intervening variable on employees at the Central Java High Court. The population used is the employees of the Central Java High Court with a total sample of 98 respondents. The analysis tool is Partial Least Square.  The urgency of this research is that there is a change in organizational restructuring, namely the separation of the secretarial structure and court clerkship which has an impact on the disharmony of the relationship between the Chair and the Secretary, which affects the behavior of employees to want to work extra roles in carrying out their duties, such as helping each other and working together with fellow employees. The novelty in this research is the addition of affective commitment variable as a mediating variable in the relationship between Islamic Work Ethics, Spiritual Leadership and Perceived Organizational Support with Organizational Citizenship Behavior. The test results show that Islamic Work Ethics, Spiritual Leadership and Perceived Organizational Support have a significant positive effect on Affective Commitment. Islamic Work Ethics, Spiritual Leadership, Perceived Organizational Support and Affective Commitment have a significant positive effect on Organizational Citizenship Behavior. Affective Commitment can be an intervening variable between Islamic Work Ethics and Organizational Citizenship Behavior. Affective Commitment can be an intervening variable between Spiritual Leadership and Organizational Citizenship Behavior. Affective commitment can be an intervening variable between Perceived Organizational Support and Organizational Citizenship Behavior.